The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.preteyeres.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine signaling and myopia development: What are the key challenges

Abstract: In the face of an “epidemic” increase in myopia over the last decades and myopia prevalence predicted to reach 2.5 billion people by the end of this decade, there is an urgent need to develop effective and safe therapeutic interventions to slow down this “myopia booming” and prevent myopia-related complications and vision loss. Dopamine (DA) is an important neurotransmitter in the retina and mediates diverse functions including development, visual signaling, and refractive development. Inspired by the converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
203
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(229 citation statements)
references
References 126 publications
7
203
1
1
Order By: Relevance
“…Our observation that the highest association with CR was with weight at 1 year of age is in line with this finding. Emmetropisation is hypothesised to be an active process of ocular scaling resulting from environmental influences, release of retinal neurotransmitters and feedback mechanisms . The results of this study feed into this hypothesis, because we found a high correlation between body growth, corneal curvature, and AL without influence on AL/CR ratio.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our observation that the highest association with CR was with weight at 1 year of age is in line with this finding. Emmetropisation is hypothesised to be an active process of ocular scaling resulting from environmental influences, release of retinal neurotransmitters and feedback mechanisms . The results of this study feed into this hypothesis, because we found a high correlation between body growth, corneal curvature, and AL without influence on AL/CR ratio.…”
Section: Discussionsupporting
confidence: 76%
“…Emmetropisation is hypothesised to be an active process of ocular scaling resulting from environmental influences, [25][26][27][28] release of retinal neurotransmitters [29][30][31] and feedback mechanisms. 32,33 The results of this study feed into this hypothesis, because we found a high correlation between body growth, corneal curvature, and AL without influence on AL/CR ratio. The small effect between birth weight and AL/CR ratio may be explained by lens parameters, as the lens is thinner with an increased birth weight.…”
Section: Larger Neonates Have a Higher Al And Greater Cr In Later Chisupporting
confidence: 74%
“…APO, as well as dopamine, also produces more consistent and effective inhibition of myopia development than other dopamine agents for all species studied so far. 4 These results also support the idea that decreased dopamine activity contributes to the development of FDM.…”
supporting
confidence: 73%
“…3,4 Retinal and vitreous dopamine and/or the dopamine metabolite 3,4-dihydroxyphenylacetic acid (DOPAC) levels are reduced during the development of FDM in various animals, including chickens, 5,6 monkeys, 7 and guinea pigs. 8 Furthermore, the decrease of retinal DOPAC was restricted only to the deprived area of the retina during partial deprivation.…”
mentioning
confidence: 99%
“…There, re‐modulation of collagen structures takes place that makes the eye longer . The molecular structure of the signalling cascade is slowly becoming clearer, and dopamine is deemed to be an important player . Animal experiments have shown that this neurotransmitter is secreted by the amacrine cells after light exposure, and acts as a stop signal for growth .…”
Section: Aetiologymentioning
confidence: 99%